ASTI Zimbabwe Database - Agricultural Science and Technology Indicators (International Food Policy Research Institute, 2014)
This dataset includes national-level time series data on researcher capacity by qualification level, age bracket, discipline mix, and commodity, as well as a detailed breakdown of agricultural research investment across government, higher education, nonprofit, and (where possible) private for-profit agricultural research agencies. These data were derived through a series of primary survey rounds conducted by IFPRI’s Agricultural Science and Technology Indicators (ASTI) and in close collaboration with a large network of national collaborators. The ASTI data constitute a powerful resource for national and regional research managers, policymakers, donor organizations, and other stakeholders. ASTI’s key indicators provide both a diagnostic tool for assessing the allocation and use of existing resources and an advocacy tool for increasing resources and improving the efficiency and effectiveness of resource use. The ASTI website offers interactive pages that allow users to access country-level time series data, make cross-country comparisons, create graphs, and download country datasets and publications as well as detailed institutional information on agencies involved in agricultural research. The interactive benchmarking tool on the ASTI website is a convenient map-based instrument allowing users to make cross-country comparisons and rankings based on a wide set of financial and human resource indicators. The detailed ASTI datasets are available in an easy-to-use data download tool. Detailed information on definitions, methodology, and calculation procedures are available at www.asti.cgiar.org